The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/jssc.200600461
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation of dansyl amino acids in capillary electrophoresis using mono‐(3‐methyl‐imidazolium)‐β‐cyclodextrin chloride as selector

Abstract: Enantioseparations of fourteen dansyl amino acids were achieved by using a positively-charged single-isomer beta-cyclodextrin, mono-(3-methyl-imidazolium)-beta-cyclodextrin chloride, as a chiral selector. Separation parameters such as buffer pH, selector concentration, separation temperature, and organic modifier were investigated for the enantioseparation in order to achieve the maximum possible resolution. Chiral separation of dansyl amino acids was found to be highly dependent on pH since the degree of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 38 publications
(20 reference statements)
0
29
1
Order By: Relevance
“…The optimum buffer pH for chiral separation varied for different series of CDs. For Series I CDs, MIMCDCl (5a) was found to present best resolution abilities towards dansyl amino (Dns-amino) acids at pH l8.0 [40], whilst towards the same analytes, the other Series I CDs enjoyed better enantioseparation abilities at pH 6.0 [41]. For Series II CDs, excellent separations were achieved for most hydroxyl and carboxylic acids at pH in the range of 5.0l7.0.…”
Section: Choice Of Buffer In Chiral Cementioning
confidence: 93%
See 1 more Smart Citation
“…The optimum buffer pH for chiral separation varied for different series of CDs. For Series I CDs, MIMCDCl (5a) was found to present best resolution abilities towards dansyl amino (Dns-amino) acids at pH l8.0 [40], whilst towards the same analytes, the other Series I CDs enjoyed better enantioseparation abilities at pH 6.0 [41]. For Series II CDs, excellent separations were achieved for most hydroxyl and carboxylic acids at pH in the range of 5.0l7.0.…”
Section: Choice Of Buffer In Chiral Cementioning
confidence: 93%
“…Interestingly, when we made a comparison on the resolution ability of our synthesized mono-6-amino-b-CD hydrochlorides [35], mono-6-alkylamino-b-CDs [34, 42 -44], and mono-6-alkylimidazolium-b-CDs [33,40,41] towards Dnsamino acids, it was found that Series I CDs with shorter alkyl chain (R = C n H 2n+1 , n = 4) and ALAMCDCl provided the outstanding resolutions to Dns-amino acids. Similar results can also be found in the imidazoyl directly linked 6-deoxy-6-[4-(2-aminoethyl)imidazoyl]-b-CD (CD-mh), which showed more powerful resolution abilities towards Dns-amino acids than amino directly linked 6-deoxy-6-N-histamino-b-CD (CD-hm) [50].…”
Section: Concerns Of CD In Chiral Cementioning
confidence: 99%
“…Mono-6-(1-butyl-3-imidazolium)-6-deoxyb-CD was also an effective chiral selector for DNS-amino acids at pH 9.6 [47]. Studying the enantioresolution of DNS-amino acids by the methyl derivative mono-6-(1-methyl-3-imidazolium)-6-deoxy-b-CD (MIM-b-CD) it was noted that increasing the pH of the BGE between pH 6.0 and 9.5 resulted in an increase in the resolution, R S , maximizing about pH 8 and decreasing thereafter [49]. Most analytes could be baseline resolved at pH 8 using MIM-b-CD concentrations between 3 and 10 mM.…”
Section: New CD Derivativesmentioning
confidence: 98%
“…For an indirect enantioseparation, a selector is usually also necessary to resolve the derivatives. Selectors that are suitable for direct and indirect enantioseparation include cyclodextrins (CD) [12][13][14], crown ethers [15][16][17], macrocyclic antibiotics [18][19][20], chiral surfactants [21,22] and ligand-exchange complexes [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%